Efeitos de sistemas de preparo do solo no potencial matricial de um Latossolo Vermelho (Oxisol) - Alves, M. C. [UNESP] (2002)
The present work aimed to investigate which was the soil tillage system that better fits for conditions of intensive agriculture, on the region of Selviria-MS. The main objective of this paper was to study the conservation and availability of water in the soil profile. In order to evaluate the soil matric potential in field conditions, readings were accomplished, using tensiometers with a mercury gauger. Matric potential was measured at 0.10 m depth, during the vegetative period of Triticum aestivum L. and at four depths 0.10; 0.20; 0.30 e 0.40 m during the vegetative period of Phaseolus vulgaris L. The study areas were located in the municipal district of Selviria, MS, Brazil. The used experimental set-up was entirely random designed, with treatments disposed in strips; three treatments and four repetitions were used. In the different treatments, soil matric potential was determined. Result allow to conclude that the water matric potential was highest for no-tillage and minimum tillage; however, it was also shown that these two tillage systems, allowed to conserve more water in the soil, when compared to the conventional tillage. In the last cycle of the Phaseolus vulgaris L. crop, no-tillage presented smaller storage of water in the soil, compared to the minimum tillage.